2022
DOI: 10.1007/s11356-022-23386-x
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on the role of electric vehicles in alleviating environmental pollution: evidence from five leading economies

Abstract: The relationship between battery electric vehicles (BEV) and carbon dioxide emission (CO 2 ) has significant environmental outcomes. Notwithstanding, battery electric vehicles have not been extensively explored through econometric approach. For countries to meet their net zero targets, it is crucial to consider the role of battery electric vehicles, renewable energy consumption, and CO 2 . As a result, it is critical to scrutinize a variety of variables that contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 97 publications
(104 reference statements)
0
10
0
Order By: Relevance
“…The ability of electric vehicles to help improve air quality in cities and towns is their main advantage. Sun et al [65] concluded that employing renewable energy during the manufacturing and battery production process would reduce CO 2 emissions, particularly in China and the USA. Battery electric vehicles were shown to be more energy-efficient.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of electric vehicles to help improve air quality in cities and towns is their main advantage. Sun et al [65] concluded that employing renewable energy during the manufacturing and battery production process would reduce CO 2 emissions, particularly in China and the USA. Battery electric vehicles were shown to be more energy-efficient.…”
Section: Discussionmentioning
confidence: 99%
“…Such that Equation (1) outlines the mathematical function of the connection between economic development (ECD), human capital (HUC), air pollution (AIP), renewable energy consumption (REC), natural resource (NRR), and Life expectancy (LEX). As suggested by prior studies, representing the variables in their logarithm forms helps to overcome heteroscedasticity and helps produce accurate estimates among the panel data set [ 22 , 61 ]. To overcome challenges with small data observation, the study used the quadratic match-sum method to adjust the yearly frequency data to logarithm form.…”
Section: Methodsmentioning
confidence: 99%
“…Lastly, in Indonesia, the research by Ref. [ 61 ] revealed that the average Indonesia can anticipate losing 2.5 years of LEX at the recent pollution levels because the air quality fails to meet the WHO guideline for a concentration of delicate particulate matter. The discussion so far has provided an overview of the effect of air pollution on LEX among all the MINT nations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CS-ARDL allows researchers to capture dynamic interactions between variables, making it particularly useful for forecasting and policy analysis. Furthermore, it addresses issues of endogeneity and non-stationarity, common challenges in empirical research, by applying a differencing approach and providing robust coefficient estimates [ 97 , 98 ]. Additionally, CS-ARDL is versatile in handling various data types, making it applicable in various fields, from economics to finance and environmental studies.…”
Section: Methodsmentioning
confidence: 99%